Pengaruh Literasi Keuangan, E-Money, dan Kontrol Diri Terhadap Perilaku Manajemen Keuangan pada Cashless Society Generasi Z Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Slamet Riyadi Surakarta - Ayu Diah Pitaloka Lestariningsih Saiman; Setyaningsih SU (Teewan Journal Solutions, 2026)
Financial management behavior is the process of planning, managing, and controlling finances within an organization or individual to optimize the use of financial resources, make appropriate investment decisions, manage income and expenses, and minimize financial risks. This study aims to analyze the influence of financial literacy, e-money, and self-control on financial management behavior in the cashless society of generation z students at the Faculty of Economics and Business, Slamet Riyadi University, Surakarta. This research is based on the Theory of Planned Behavior (TPB). The object of this study is Generation Z students of Faculty of Economics and Business Slamet Riyadi University, Surakarta. The total sample of this study consisted of 92 respondents, calculated using Slovin’s formula. The sampling technique applied was proportionate startified random sampling. Data were collacted through questionnaires. The analysis techniques used in this study were descriptive analysis, multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The hypothesis testing result show that financial literacy has no significant effect on the financial management behavior of Generation Z students at the Faculty of Economics and Business Slamet Riyadi University Surakarta, while e-money and self-control have a significant effect on their financial management behavior of Generation Z students at the faculty of Economics and Business Slamet Riyadi University, Surakarta.